Retrograde amnesia and the volume of critical brain structures. - Kopelman, MD; Lasserson, D; Kingsley, DR; Bello, F; Rush, C; Stanhope, N; Stevens, T; Goodman, G; Buckman, JR; Heilpern, G; Kendall, B; Colchester, A (2003)
There are many controversies concerning the structural basis of retrograde amnesia (RA). One view is that memories are held briefly within a medial temporal store ("hippocampal complex") before being "consolidated" or reorganised within temporal neocortex and/or networks more widely distributed within the cerebral cortex. An alternative view is that the medial temporal lobes are always involved in the storage and retrieval (reactivation) of autobiographical memories (multiple trace theory). The present study used quantitative magnetic resonance imaging (MRI) in 40 patients with focal pathology/volume loss in different sites, to examine the correlates of impairment on three different measures of RA. The findings supported the view that widespread neural networks are involved in the storage and retrieval of autobiographical and other remote memories. Brain volume measures in critical structures could account for 60% of variance on autobiographical memory measures (for incidents and facts) in diencephalic patients and for 60-68% of variance in patients with frontal lesions. Significant correlations with medial temporal lobe volume were found only in the diencephalic group, in whom they were thought to reflect thalamic changes, but not in patients with herpes encephalitis or hypoxia in whom the temporal lobes were particularly implicated. The latter finding fails to support one of the main predictions of multiple trace theory, as presently expounded.